AN ANALYSIS OF GENDER REPRESENTATION IN I LOVE JAKARTA, AN ELEMENTARY TEXTBOOK - Junita Junita; Joseph Bryant T. Pasaribu T. Pasaribu; Angela Novianita Vidiastya (Journal of English Language and Culture, 2022)
Klein (1985) believes that appropriate gender-unbiased material mostly gives students the chance to accommodate more compliant mindsets towards gender roles. This study was conducted to observe the way genders are represented in local elementary textbooks in Indonesia, especially the textbook entitled "I Love Jakarta." The method applied in this study was qualitative research that used content analysis. The approach was used to describe the content of the textbook, by using the checklist adapted from Shallaita, et al. (2021), which includes all the texts, illustrations, vocabularies, and exercises, in every chapter of the book. The writers assessed the gender representation in the first grade of an elementary school textbook according to five categories adopted from Amini and Birjandi (2012); Visibility, Firstness, Feminine/Masculine Generic Construction, Activity, Occupation on every text and pictures in the book from unit one until sixteen. The results showed that (1) in terms of visibility, male (54%) was represented more than female (46%), (2) in terms of firstness, male (around nine mentions) in the majority of the cases was mentioned first than female (around five mentions), (3) in the category of feminine/masculine generic construction, there was no case found, (4) regarding the activities portrayed in the book, both male and female characters shared their parts of doing some of the general activities; however, there were cases where some activities were portrayed of being intended mainly for males, such as doing pencak silat and lifting heavy objects. On the other hand, there were portrayals of some of the activities which were mostly intended for females because of their less-aggressive nature, such as dancing and reading a book, (5) in terms of occupations depicted in the book, some of them were represented equally by both male and female characters; however, there were occupations which were considered more manly, such as fisherman and pedicab driver, therefore portrayed by male characters. To sum up, both genders were not represented equally in terms of the five categories.